Viols nazis en Drôme (1944) - Franck Tison (Criminocorpus)
The Drôme, strategic french department, was the scene of repression particularly ruthless by the Wehrmacht and the Gestapo in 1944. In the arsenal of iniquitous methods used by the Occupying forces in order to mak people’s minds and divide the resisting population, was rape. What with “opportunistic” rape or mass-rape as in St Donat sur l’Herbasse, in the Vercors, or in the Drôme valley, this criminal practice brought about hundreds victims.The german command made use of the Ost-Legion’s Mongols giving them a free hand to carry out their crimes on women and very young girls. Such hard facts, that were conjured up during the Nuremberg trials, aroused indignation among refugee-writers in La Drôme, such as Charles de Richter or Louis Aragon.